O uso de atividades experimentais no ensino de Física para o estudante de indução eletromagnética - Melo, Paulo Henrique Pereira de (2021)
In this dissertation we present a proposal of Problematic Teaching, which has as its educational product a Didactic Sequence, which has as object of discussion the study of electromagnetic induction. The development of the conceptual basis of electromagnetic induction occurred from the realization of experimental activities, in which after numerous observations and questions raised about the phenomenon, made it possible to nderstand the union of electricity and magnetism, thus giving rise to electromagnetism. The proposed didactic sequence is composed of five meetings and follows the use of experimentation in the classroom and the three pedagogical moments of Delizoicov and Angotti. In the first four meetings, the students will handle experiments related to electromagnetism, where through the socialization of knowledge, stimulus and incentive, they will move into the process of building knowledge, seeking to explain the phenomena observed. At the end of each meeting the students will participate in an evaluation composed of questions, which must be answered in a descriptive manner and with the use of graphic representations. At the end we will have as an educational product, the didactic sequence and a tutorial for making the experiments, which follow an order of phenomena on electromagnetic induction.